The jungle is neutral a soldier's three-year jungle escape from the Japanese army - Chapman, F. Spencer (Frederick Spencer), 1907-1971 (Marshall Cavendish, 2014)
Over 25,000 copies sold! An action-packed yet highly detailed account of jungle guerilla warfare, used as a primer on jungle warfare by the French Foreign Legion. An interesting story that leads to many adventures and insight into a complex number of peoples fighting the Japanese